At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve for [tex]\(x\)[/tex], we need to determine which side is the hypotenuse in our right-angled triangle. The hypotenuse is always the longest side of the triangle. Given the sides [tex]\(x + 4\)[/tex] cm, [tex]\(x - 1\)[/tex] cm, and 6 cm, it is clear that 6 cm is the largest, so it must be the hypotenuse.
Using the Pythagorean theorem, which states:
[tex]\[ a^2 + b^2 = c^2 \][/tex]
Assign [tex]\(a = x + 4\)[/tex], [tex]\(b = x - 1\)[/tex], and [tex]\(c = 6\)[/tex]. Now substitute these values into the Pythagorean theorem:
[tex]\[ (x + 4)^2 + (x - 1)^2 = 6^2 \][/tex]
Expand each term on the left-hand side:
[tex]\[ (x + 4)^2 = x^2 + 8x + 16 \][/tex]
[tex]\[ (x - 1)^2 = x^2 - 2x + 1 \][/tex]
Add these results together:
[tex]\[ x^2 + 8x + 16 + x^2 - 2x + 1 = 36 \][/tex]
Combine like terms:
[tex]\[ 2x^2 + 6x + 17 = 36 \][/tex]
Now, subtract 36 from both sides to set the equation to 0:
[tex]\[ 2x^2 + 6x + 17 - 36 = 0 \][/tex]
[tex]\[ 2x^2 + 6x - 19 = 0 \][/tex]
This is a quadratic equation, which can be solved using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For [tex]\(a = 2\)[/tex], [tex]\(b = 6\)[/tex], and [tex]\(c = -19\)[/tex], let's plug these values into the formula:
First, calculate the discriminant:
[tex]\[ b^2 - 4ac = 6^2 - 4(2)(-19) = 36 + 152 = 188 \][/tex]
Now apply the quadratic formula:
[tex]\[ x = \frac{-6 \pm \sqrt{188}}{2 \cdot 2} = \frac{-6 \pm \sqrt{188}}{4} \][/tex]
Simplify the square root term and the fraction:
[tex]\[ x = \frac{-6 \pm 2\sqrt{47}}{4} => x = \frac{-3 \pm \sqrt{47}}{2} \][/tex]
There are two solutions to this equation:
[tex]\[ x = \frac{-3 + \sqrt{47}}{2} \][/tex]
[tex]\[ x = \frac{-3 - \sqrt{47}}{2} \][/tex]
Since [tex]\(x\)[/tex] must be positive (as it represents a length), we only consider the positive solution:
[tex]\[ x = \frac{-3 + \sqrt{47}}{2} \][/tex]
To find the numerical value, we approximate:
[tex]\[ \sqrt{47} \approx 6.856 \][/tex]
So:
[tex]\[ x \approx \frac{-3 + 6.856}{2} \approx \frac{3.856}{2} \approx 1.928 \][/tex]
Therefore, to three significant figures, the value of [tex]\(x\)[/tex] is:
[tex]\[ x \approx 1.93 \][/tex]
Using the Pythagorean theorem, which states:
[tex]\[ a^2 + b^2 = c^2 \][/tex]
Assign [tex]\(a = x + 4\)[/tex], [tex]\(b = x - 1\)[/tex], and [tex]\(c = 6\)[/tex]. Now substitute these values into the Pythagorean theorem:
[tex]\[ (x + 4)^2 + (x - 1)^2 = 6^2 \][/tex]
Expand each term on the left-hand side:
[tex]\[ (x + 4)^2 = x^2 + 8x + 16 \][/tex]
[tex]\[ (x - 1)^2 = x^2 - 2x + 1 \][/tex]
Add these results together:
[tex]\[ x^2 + 8x + 16 + x^2 - 2x + 1 = 36 \][/tex]
Combine like terms:
[tex]\[ 2x^2 + 6x + 17 = 36 \][/tex]
Now, subtract 36 from both sides to set the equation to 0:
[tex]\[ 2x^2 + 6x + 17 - 36 = 0 \][/tex]
[tex]\[ 2x^2 + 6x - 19 = 0 \][/tex]
This is a quadratic equation, which can be solved using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For [tex]\(a = 2\)[/tex], [tex]\(b = 6\)[/tex], and [tex]\(c = -19\)[/tex], let's plug these values into the formula:
First, calculate the discriminant:
[tex]\[ b^2 - 4ac = 6^2 - 4(2)(-19) = 36 + 152 = 188 \][/tex]
Now apply the quadratic formula:
[tex]\[ x = \frac{-6 \pm \sqrt{188}}{2 \cdot 2} = \frac{-6 \pm \sqrt{188}}{4} \][/tex]
Simplify the square root term and the fraction:
[tex]\[ x = \frac{-6 \pm 2\sqrt{47}}{4} => x = \frac{-3 \pm \sqrt{47}}{2} \][/tex]
There are two solutions to this equation:
[tex]\[ x = \frac{-3 + \sqrt{47}}{2} \][/tex]
[tex]\[ x = \frac{-3 - \sqrt{47}}{2} \][/tex]
Since [tex]\(x\)[/tex] must be positive (as it represents a length), we only consider the positive solution:
[tex]\[ x = \frac{-3 + \sqrt{47}}{2} \][/tex]
To find the numerical value, we approximate:
[tex]\[ \sqrt{47} \approx 6.856 \][/tex]
So:
[tex]\[ x \approx \frac{-3 + 6.856}{2} \approx \frac{3.856}{2} \approx 1.928 \][/tex]
Therefore, to three significant figures, the value of [tex]\(x\)[/tex] is:
[tex]\[ x \approx 1.93 \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.